Regulation of Sympathetic Nerve Activity in Heart Failure - Jun‐Li Liu; Irving H. Zucker (1999)
The mechanisms by which sympathetic function is augmented in chronic heart failure (CHF) are not well understood. A previous study from this laboratory (Circ Res. 1998;82:496-502) indicated that blockade of nitric oxide (NO) synthesis resulted in only an increase in renal sympathetic nerve activity (RSNA) when plasma angiotensin II (Ang II) levels were elevated. The present study was undertaken to determine if NO reduces RSNA in rabbits with CHF when Ang II receptors are blocked. Twenty-four New Zealand White rabbits were instrumented with cardiac dimension crystals, a left ventricular pacing lead, and a pacemaker. After pacing at 360 to 380 bpm for approximately 3 weeks, a renal sympathetic nerve electrode and arterial and venous catheters were implanted. Studies were carried out in the conscious state 3 to 7 days after electrode implantation. The effects of a 1-hour infusion of sodium nitroprusside (SNP; 3 microgram . kg-1. min-1) on RSNA and mean arterial pressure (MAP) were determined before and after Ang II blockade with losartan (5 mg/kg) in normal and CHF rabbits. Changes in MAP were readjusted to normal with phenylephrine. Before losartan, SNP evoked a decrease in MAP and an increase in RSNA in both groups that was baroreflex-mediated, because both MAP and RSNA returned to control when phenylephrine was administered. In the normal group, losartan plus SNP caused a reduction in MAP and an increase in RSNA that was 152.6+/-9.8% of control. Phenylephrine returned both MAP and RSNA back to the control levels. However, in the CHF group, losartan plus SNP evoked a smaller change in RSNA for equivalent changes in MAP (117.1+/-4.1% of control). On returning MAP to the control level with phenylephrine, RSNA was reduced to 65.2+/-2.9% of control (P<0. 0001). These data suggest that endogenous Ang II contributes to the sympathoexcitation in the CHF state and that blockade of Ang II receptors plus providing an exogenous source of NO reduces RSNA below the elevated baseline levels. We conclude that both a loss of NO and an increase in Ang II are necessary for sustained increases in sympathetic nerve activity in the CHF state.